1987
DOI: 10.1007/bf02014255
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of four fluoroquinolones against eighty-six isolates of mycobacteria

Abstract: The in vitro activity of pefloxacin, norfloxacin, ofloxacin and ciprofloxacin against 86 strains of mycobacteria was evaluated by broth dilution. While Mycobacterium avium, Mycobacterium scrofulaceum and Mycobacterium chelonae were resistant to all four antibacterials, the susceptibility of the other species, Mycobacterium tuberculosis, Mycobacterium kansasii, Mycobacterium xenopi and Mycobacterium fortuitum, depended on the antibiotic. Ofloxacin and ciprofloxacin (MIC90: 0.5 - 2 mg/l) were more active than pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Despite these aggravating circumstances, the five remaining patients did convert to negative, which fact was considered by the authors of the paper as evidence that A. pH 6. (1,3,5,7,8,9,14,22,23,26,28). The 29.1% for ciprofloxacin, and 85.5% for Win 57273.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these aggravating circumstances, the five remaining patients did convert to negative, which fact was considered by the authors of the paper as evidence that A. pH 6. (1,3,5,7,8,9,14,22,23,26,28). The 29.1% for ciprofloxacin, and 85.5% for Win 57273.…”
Section: Resultsmentioning
confidence: 99%
“…The MICs of these two drugs were found to be within the same range when tested against Mycobacterium tuberculosis in liquid media (3,14,26), in agar plates (1,5,7,14,22,23), and in Lowenstein-Jensen medium (27; R. D. Urbanczik, Abstr. XXVI Int.…”
mentioning
confidence: 89%
“…strain 7E1B1W and Mycobacterium sp. strain PYR100) and Mycobacterium smegmatis mc 2 155 were less susceptible to norfloxacin than most of the clinical isolates tested by TexierMaugein et al (36). Because norfloxacin enters mycobacterial cells quickly by simple diffusion (38), the abilities of these strains to transform norfloxacin may partly explain their resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Some discrepancies may be the result of differences in method. It is, however, shown that MICs vary little, regardless of whether agar or broth dilution was used (48 (2,9,13,16,22,25,37,52,66). However, since different comparison agents were used in these studies it is difficult to be certain about the activities of these compounds in relation to the parent compounds.…”
Section: Vitro Activitymentioning
confidence: 99%